Improving the Poetry Writing Skills of Grade 3 Students Through Animation Image Media at SDN Ngembeh 1 - Jayanti, Rani; Yahya, Yuwafa Faurelio; Kholis, M Nur; Khanif, Misbahul; Saufaqillah, Iktarna Faris (Jurnal Pengabdian Masyarakat Bestari, 2024)
The development of Indonesian Language literacy at the elementary level requires an important aspect, namely learning to write poetry. An approach that has begun to be introduced is Project Based Learning, which aims to improve students' understanding of concepts and skills through real experiences. Related to the purpose of the research, which is to examine the teacher's response and examine the difficulties experienced by students in learning to write poetry using the PBL model at SDN Ngembeh 1. The subjects in the study were 13 students. Conducting qualitative descriptive methods. The data analyst used is in the form of scores from test results carried out as the final result. The results of the test of 13 students in learning to write poetry, as many as five students got a score below the KKM. It was concluded that learning to write poetry using the PBL method with the help of animation image media is quite effective in learning to write poetry.